Luxembourg as an aspiring platform for the aircraft engine industry - Peter Koster (European Institute for Knowledge & Value Management (EIKV), 2016)
This document represents the results of the a study project carried out to conclude the ability of Luxembourg potential to diversify it's todays aviation industry and create or access synergies that may or may not yet be present. The document aims equally to assess and bring forward shortcomings but also strength that Luxembourg in its current economical environment holds. This study is an original intellectual product of the author; the document is ultimately based on the apparatus and data made available by industry experts and industry published articles. The document has been subdivided into two main parts and the respective subtitles. It is attempting to translate a very specific industry segment, and its particularities, into a comprehensive document to an audience of non-expert and non-industry readers. The aim is to establish a comprehensive understanding of how a specific commodity within the aviation industry can form a particular asset and how this asset could be capitalized in a given environment, fully or partially, available in Luxembourg.
Keywords: 650